HUBUNGAN STRES KERJA DENGAN PERILAKU PRESENTEEISM PERAWAT RUMAH SAKIT X MAKASSAR - Gledy Febriani Buranda; Muhammad Jufri; Nur Afni Indahari (Politeknik STIA LAN Makassar, 2018)
Nurse is a job susceptible to occupational stress for timing pressure and high burden of workload. Occupational stress of nurses could force them into presenteeism behavior, the condition when employee push themself to still working although not in good and healthy condition. The aim of this study was to find correlation between occupational stresses with nurses presenteeism. Samples of this study were 50 nurses of inpatient room of X Hospital in Makassar which taken by using total sampling method. Measuring instruments used in this study were nurses job stress scale (Î± = 0,859) and presenteeism scale (Î± = 0,816). Using hypothetical test of Spearman correlation, results found r = 0,653 and p = < 0,05. The result means there was positive correlation between occupational stresses with nurses presenteeism on X Hospital in Makassar. Presenteeism can affect the productivity of nurses, so it is important for hospitals to control the nurses occupational stress to reduce the appearance of presenteeism and avoid the negative impact of presenteeism.